Sex-specific Associations of Sex Hormone Binding Globulin with CKD and Kidney Function: A Univariable and Multivariable Mendelian Randomization Study in the UK Biobank - Zhao, Jie V. (J Am Soc Nephrol, 2021)
BACKGROUND: Kidney function declines faster in men. Testosterone levels may mediate the sex disparity. Correspondingly, levels of sex hormone binding globulin (SHBG), which modulates sex hormones, might also be relevant to the lower kidney function in men. The sex-specific role of SHBG is unclear. METHODS: A sex-specific, Mendelian randomization (MR) study provided unconfounded estimates of SHBG levels among the United Kingdom Biobank population. Univariable MR applied 357 single nucleotide polymorphisms (SNPs) in men and 359 SNPs in women. These published SNPs strongly (P<5×10(−8)) predict SHBG level. They were profiled in 179,916 white British men (6016 patients with CKD) and 212,079 white British women (5958 patients with CKD), to obtain the effect of SHBG on CKD, albuminuria, and eGFR. Multivariable MR controlling for testosterone was used to assess the effect of SHBG on CKD and kidney function independent of testosterone in men. RESULTS: Genetically predicted higher SHBG was associated with a lower risk of CKD in men (odds ratio [OR], 0.78 per SD; 95% confidence interval [95% CI], 0.65 to 0.93) but had no benefit in women. The effect in men remained in multivariable MR, allowing for testosterone (OR, 0.61; 95% CI, 0.45 to 0.82). CONCLUSIONS: Genetically predicted higher SHBG was associated with a lower risk of CKD and better kidney function in men, but not in women, suggesting that SHBG may play a role in CKD specifically in men. Identifying drivers of SHBG and the underlying pathways could provide new insights into CKD prevention and treatment.